(untitled) (AmS-Varia, 2019)
In Rogaland County, southwestern Norway, one of the country’s largest collections of rock art can be found: ca. 110 sites with figures and cup marks, 38 grave monuments with decorated slabs or stones with cup marks (altogether 67 slabs) and 37 stray finds of decorated slabs or stones with cup marks. In 1996, the Museum of Archaeology, University of Stavanger established an interdisciplinary group working primarily on the documentation and preservation of rock art. This group was part of the National Rock Art Project, a program run by the Norwegian Directorate for Cultural Heritage. The project lasted until 2005, after which the Directorate granted supplemental funds for continuing the work. Two previous papers have been published concerning rock art in Rogaland (AmS-Rapport 9 and AmS-Rapport 19). In this publication, we will present 15 sites with figures and cup marks, 20 with cup marks only and 61 decorated slabs and stones with cup marks recovered from either grave monuments or as stray finds. Ships are the most common motive, but the range of motives also includes simple discs, wheel crosses and, more rarely, human figures, horses and axes. As far as possible, these sites are put into an environmental context in terms of vegetation history, sea-level fluctuations and geological conditions. Furthermore, the publication contains an historical outline of earlier investigations and documentation as well as descriptions and the present status from the rock art sites. Damage and weathering are also described. Finally, we present interpretations of the symbolism and cultural background of the rock art.